ESP Learner Motivations and Perceptions towards International Online Letter Exchange Program - Ruminar, Hafida; Gayatri, Putri; Prasetyaningrum, Dian Islami (JET ADI BUANA, 2020)
The Online Letter Exchange Program (OLEP) was an online collaborative learning program hosted by the Faculty of Agriculture of the University of Miyazaki, Japan. It has collaborated with the Faculty of Agriculture in one of the private universities in Malang. The program is designed to encourage students’ written communication skills and facilitate students with intensive real-life English communication experience with other students around Asia. The participant countries are from Japan, Taiwan, China, and Indonesia. One of its uniqueness lies in the policy that the participants share their specific fields, including agriculture and related fields. This study sought to investigate the intrinsic and extrinsic gacor5000 motivation and perception of the students towards the OLEP as it was supplementary activity. The perception included the topic, the platform, and interaction. The data were gained from questionnaires and interviews and were then analyzed using thematic analysis. The result showed that extrinsic motivation was dominant in completing the task in OLEP. The positive and negative perception of the three aspects would be a valuable source for those who attempt a similar online letter exchange program